2013
DOI: 10.1093/ejcts/ezt063
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan-coated sutures reduce surgical site infection after open vein harvesting in coronary artery bypass grafting patients: a randomized controlled trial†

Abstract: OBJECTIVESThe incidence of surgical site infection (SSI) after open vein harvesting in coronary artery bypass grafting (CABG) patients ranges in different studies between 2 and 20%. Triclosan is an antibacterial substance that reduces the growth of bacteria by inhibiting fatty acid synthesis. We hypothesized that wound closure with triclosan-coated sutures would reduce SSI after open vein harvesting.METHODSAn investigator-initiated prospective randomized double-blind single-centre study was performed with 374 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 26 publications
0
54
0
1
Order By: Relevance
“…Pre-clinical studies have shown that triclosan-coated sutures reduce the growth of gram-positive and gram-negative bacteria [9,10]. These studies have been followed by retrospective series and prospective controlled trials in different surgical populations to test whether triclosan-coated sutures reduce incisional SSIs; however, results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have shown that triclosan-coated sutures reduce the growth of gram-positive and gram-negative bacteria [9,10]. These studies have been followed by retrospective series and prospective controlled trials in different surgical populations to test whether triclosan-coated sutures reduce incisional SSIs; however, results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Es könnte deshalb mit seiner Verwendung zur Reduktion des SSI-Risikos kommen. Die diesbezügliche Studienlage ist uneinheitlich [192][193][194][195][196][197][198][199][200][201]. Die WHO empfiehlt die Verwendung unabhängig von der Art der Operation [40], das CDC in der Viszeralchirurgie [202].…”
Section: Op-handschuheunclassified
“…Thimour-Bergström et al [6] conducted a randomized double-blinded study including 374 coronary artery bypass surgery patients. They reported that leg surgical incision closure with triclosan-coated sutures reduces SSI rate after open vein harvesting.…”
mentioning
confidence: 99%
“…This study, not included in the meta-analysis, reported that the occurrence of SSI after abdominal wall closure did not differ between the triclosan-coated group and the control group. The meta-analysis would have resulted with the conclusion that the use of triclosan-coated sutures does not decrease the incidence of SSI if the study by Diener et al [8] included in the analysis and the studies of Zhuang et al [2], Isik et al [7], and Thimour-Bergström et al [6] were interpreted as ''non-triclosan-favoring'' and the studies of Rasic et al [3] and Galal et al [5] were excluded from the analysis.…”
mentioning
confidence: 99%